2017
DOI: 10.5455/aim.2017.25.267-270
|View full text |Cite
|
Sign up to set email alerts
|

Presenting an Evaluation Model for the Cancer Registry Software

Abstract: Objectives:As cancer is increasingly growing, cancer registry is of great importance as the main core of cancer control programs, and many different software has been designed for this purpose. Therefore, establishing a comprehensive evaluation model is essential to evaluate and compare a wide range of such software.Methods:In this study, the criteria of the cancer registry software have been determined by studying the documents and two functional software of this field. The evaluation tool was a checklist and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…On the one hand, to facilitate the platform uses in our native language (Spanish), limit annual spending, and include speci c details related to the institutional research and administrative needs, a multidisciplinary institutional team developed a custom software platform (SIRIC) for our HBCR. On the other hand, a novel proposal to evaluate cancer registry software made by researchers from Iran was considered for our platform's development [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, to facilitate the platform uses in our native language (Spanish), limit annual spending, and include speci c details related to the institutional research and administrative needs, a multidisciplinary institutional team developed a custom software platform (SIRIC) for our HBCR. On the other hand, a novel proposal to evaluate cancer registry software made by researchers from Iran was considered for our platform's development [45].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, different strategic actors of Cali joined through the initiative City Cancer Challenge 2025 (C/Can 2015), whose purpose is to design, plan, and implement better solutions for cancer care in the region [45]. The initiative has in their city objectives, the creation of an integrated information system for oncological services management where HBCRs have a crucial role in their development.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, diabetes kills one person every 10 seconds [4,5]. Further, a large body of research indicated that actions are needed by means of diagnosing, preventing, and monitoring the diabetes accurately in order to prevent or delay the acute and chronic complications [5][6][7][8][9]. Further, the availability of adequate and accurate information about the patients, the nature of the disease, and time and location is regarded as an important factor in developing and implementing effective strategies for preventing and controlling a disease.…”
Section: Introductionmentioning
confidence: 99%